Churchill - Johnson, Paul, 1928-2023 (New York : Recorded Books, 2009)
Starred Review. In this enthusiastic yet first-rate biography, veteran British historian Johnson (Modern Times) asserts that Winston Churchill (18741965) was the 20th century's most valuable figure: No man did more to preserve freedom and democracy.... An ambitious, world-traveling soldier and bestselling author, Churchill was already famous on entering Parliament in 1899 and within a decade was working with Lloyd George to pass the great reforms of 19081911. As First Lord of the Admiralty, he performed brilliantly in preparing the navy for WWI, but blameundeserved according to Johnsonfor the catastrophic 1915 Dardanelles invasion drove him from office. Within two years, he was back at the top, where he remained until the Depression. Johnson delivers an adulatory account of Churchill's prescient denunciations of Hitler and heroics during the early days of WWII, and views later missteps less critically than other historians. He concludes that Churchill was a thoroughly likable great man with many irritating flaws but no nasty ones: he lacked malice, avoided grudges, vendettas and blame shifting, and quickly replaced enmity with friendship. Biographers in love with their subjects usually produce mediocre history, but Johnson, always self-assured as well as scholarly, has written another highly opinionated, entertaining work
Young thruster -- Liberal statesman -- The lessons of failure -- Success and disasters -- The unregarded prophet -- Supreme power and frustration -- Glorious twilight.
Includes bibliographical references and index.
Keywords: Churchill, Winston, -- 1874-1965; Prime ministers -- Great Britain -- Biography; Great Britain -- Politics and government -- 20th century